Detection and treatment strategies of per- and polyfluoroalkyl substances (PFAS): fate of PFAS through DPSIR framework analysis - John, Juliana; Coulon, Frederic; Chellam, Padmanaban Velayudhaperumal (Elsevier, 2021)
Per/polyfluoroalkyl substances (PFAS), regarded as “forever chemicals”, are a class of emerging contaminants occurring worldwide that pose many serious environmental issues to water quality and human health. The presence of strong carbon‑fluorine bonds in their backbone and their physicochemical properties offer them resistance and restrict them from breaking down into simple compounds in the environment. There are many challenges to be addressed in the detection and removal from the environment. In this comprehensive review, a Driver-Pressure-State-Impact-Response (DPSIR) framework has been proposed to understand PFAS from the source of emission and their impacts on the environment. We reviewed the various detection methodologies for monitoring PFAS levels and analytical techniques for their quantification to know their environmental levels. The challenges and scope of various treatment technologies developed and implemented have also been critically discussed. The future perspectives of PFAS, including their source reduction and framing regulatory policies and the challenges faced when moving towards a sustainable future, are focused.
Keywords: PFAS; DPSIR; framework; Sensors; Optimization; Treatment technologies; Regulatory standards